2017
DOI: 10.18632/oncotarget.21436
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8 is required for survival and radioresistance of glioblastoma cells

Abstract: TRPM8 is a Ca2+-permeable nonselective cation channel belonging to the melastatin sub-group of the transient receptor potential (TRP) family. TRPM8 is aberrantly overexpressed in a variety of tumor entities including glioblastoma multiforme where it reportedly contributes to tumor invasion. The present study aimed to disclose further functions of TRPM8 in glioma biology in particular upon cell injury by ionizing radiation. To this end, TCGA data base was queried to expose the TRPM8 mRNA abundance in human glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 42 publications
3
50
0
2
Order By: Relevance
“…CaMKII-mediated inhibitory phosphorylation of cdc25 phosphatases [cdc25B in K562 CML (Palme et al, 2013) and Jurkat T cell leukemia (Klumpp et al, 2016), and probably cdc25C in glioblastoma cells (Klumpp et al, 2017)] prevents the activating dephosphorylation of the cdc25 target p-(Tyr15)-cdc2 as also observed in the present study. Cdc2 together with cyclin B forms the mitosis-promoting factor, and the inhibitory phosphorylation results in G 2 /M arrest of the cell cycle (Palme et al, 2013;Klumpp et al, 2016;Klumpp et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…CaMKII-mediated inhibitory phosphorylation of cdc25 phosphatases [cdc25B in K562 CML (Palme et al, 2013) and Jurkat T cell leukemia (Klumpp et al, 2016), and probably cdc25C in glioblastoma cells (Klumpp et al, 2017)] prevents the activating dephosphorylation of the cdc25 target p-(Tyr15)-cdc2 as also observed in the present study. Cdc2 together with cyclin B forms the mitosis-promoting factor, and the inhibitory phosphorylation results in G 2 /M arrest of the cell cycle (Palme et al, 2013;Klumpp et al, 2016;Klumpp et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…These on the first view conflicting data might reflect a highly complex regulation of the CaMKIIs by Ca 2+ that require both, K v 3.4 and hERG1 channels. Nucleustranslocated CaMKII isoforms have shown previously and in the present study to regulate cell cycle in irradiated K562 CML [(Heise et al, 2010) and present study], Jurkat T cell leukemia (Klumpp et al, 2016), and glioblastoma cells (Klumpp et al, 2017). CaMKII-mediated inhibitory phosphorylation of cdc25 phosphatases [cdc25B in K562 CML (Palme et al, 2013) and Jurkat T cell leukemia (Klumpp et al, 2016), and probably cdc25C in glioblastoma cells (Klumpp et al, 2017)] prevents the activating dephosphorylation of the cdc25 target p-(Tyr15)-cdc2 as also observed in the present study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Activities of TRPM8 were required for the chemotaxis and migration of glioblastoma cells (T98G and U-87MG) as shown by siRNA-mediated downregulation of TRPM8, pharmacological inhibition by the TRP channel blocker BCTC or TRPM8 activation by icilin (Klumpp et al, 2017). The authors reported that TRPM8 promoted migration of these glioblastoma cells possibly through activation of Ca 2+ -regulated K + channel, that is, big conductance Moreover, independent groups of researchers demonstrated that TRPM8 short isoforms localized in the cytoplasm (in contrast to the full-length TRPM8 localized on the plasma membrane) were required for the survival, migration, and invasion of prostate cancer cells (LNCaP; Bidaux et al, 2016;Peng et al, 2015).…”
Section: Trpm8: Oncogenic Cytoplasmic Localization and Short Isoformsmentioning
confidence: 99%
“…The same study also demonstrated that TRPM8 conferred resistance to ionizing radiation and survival of U251 glioblastoma cells. TRPM8 contributed to the S-phase progression of the cell cycle and mitosis of glioblastoma cells via induction of CaMKII isoforms, cdc25C (phosphatase) and cdc2 (cyclin-dependent kinase;Klumpp et al, 2017).Several lines of evidence have demonstrated TRPM8 to have important functions in the development and progression of tumors, and it is an emerging therapeutic target particularly in prostate cancer. TRPM8 is overexpressed in prostate tumors compared to nonmalignant prostate tissues, and the protein is present in hormone-refractory prostate cancer and in cases with higher Gleason scores(Yee, 2015).…”
mentioning
confidence: 99%